1988
DOI: 10.1016/0014-5793(88)80796-8
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the high‐affinity agonist state of the α1‐adrenergic receptor at cold temperatures does not require a G‐protein

Abstract: Two methods were employed to uncouple hepatic cq-adrenergic receptors from their associated G-protein (termed Gv) in order to determine whether locking of the ~l-receptor in a high-affinity agonist state at cold temperatures (2°C) represents formation of a ternary complex. Uncoupling is defined as the inability to observe the GppNHp-sensitive, highaffinity agonist state of the receptor in pH]prazosin competition binding studies performed at 25°C. The first method for achieving uncoupling involved brief alkalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
2

Year Published

1988
1988
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
(50 reference statements)
0
9
2
Order By: Relevance
“…There was no difference in the ratio of high-and low-affinity receptors measured either at 40C or 250C, with all receptors converting to the low-affinity state at 370C. Our results differ somewhat from another report published by Lynch et al (1988) Lynch et al (1985), a mixed population of high-and low-affinity receptors in binding studies conducted at 250C. We measured the same mixed population at 40C.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…There was no difference in the ratio of high-and low-affinity receptors measured either at 40C or 250C, with all receptors converting to the low-affinity state at 370C. Our results differ somewhat from another report published by Lynch et al (1988) Lynch et al (1985), a mixed population of high-and low-affinity receptors in binding studies conducted at 250C. We measured the same mixed population at 40C.…”
Section: Discussioncontrasting
confidence: 57%
“…In contrast, changes with age in the xl-receptor may or may not result in altered al control of glycogenolysis. Lynch et al (1988) reported that noradrenaline-stimulated phosphorylase activity in isolated hepatocytes is unchanged with age. This is consistent with our finding that adrenaline-stimulated PI hydrolysis in liver slices prelabelled with [3H]-myoinositol is also unchanged with age (unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…pINHlppG promotes the dissociation of receptor-G-protein-agonist complexes (18). Similarly, exposure of membrane preparations to a high pH can inactivate G proteins, leaving P-, a,-, and aradrenergic receptors intact but lacking high-affinity agonist binding (19,20) Fig. 2A and Table 1).…”
mentioning
confidence: 99%
“…2B), indicating a conversion of the receptor to a higher‐affinity conformation. Similarly, low temperature‐induced conversion of the α 1 ‐adrenergic receptor to a single agonist high‐affinity state was not dependent on the presence of a G protein (Lynch et al, 1988). Rigidification of the membrane bilayer or low temperature may create a condition in the lipid surrounding the receptor where increased lateral pressure (Yeagle, 1991) directly alters the equilibrium between low‐ and high‐affinity receptor conformations, leading to the stabilization of a G protein‐independent agonist high‐affinity state.…”
Section: Discussionmentioning
confidence: 99%